Slope Variations at Bangsaen Beach during the Year 2002 to 2014 - Jintasaeranee, Pachoenchoke; Piyapong, Chantima (Burapha Science Journal, 2026)
Variations of depth at Bangsaen beach during the year 2002 to 2014 were determined in the areas of Bangsaen and Vonnapa beaches. The results show that the slopes at Bangsaen beach in 2014 are varied larger than in 2002. Laemtan beach and Bangsaen beach show a larger slope variation within 2 monsoon seasons while shows changes some of slope at Vonnapa beach in North East monsoon, and shows a little change of slope in the middle part of Bangsaen beach adjacent to the Bangsaen. Waves and longshore currents could be a major influence that induces some sediment from Bangsaen and Vonnapa beachs resulting to the area of Bangsaen roundabout shows less variation. The slope variations at Bangsaen beach show the need of the additional studies within nearshore waves, longshore currents, longshore sediment transports, coastal erosions, an equilibrium bay and coastal managements of Bangsaen beach.